The mediating role of serum 25-hydroxyvitamin D on the association between reduced sensitivity to thyroid hormones and periodontitis in Chinese euthyroid adults - Yang, Hao; Lu, Yayun; Zhao, Lina; He, Yufeng; He, Yuecheng; Chen, Dong (Frontiers in Endocrinology, 2024)
Aim Thyroid dysfunction is closely associated with periodontitis. We aim to explore the association between sensitivity to thyroid hormones (THs) and periodontitis and to investigate the mediating role of serum 25-hydroxyvitamin D[25(OH)D] in this relationship in Chinese euthyroid populations. Methods This population-based retrospective study included 2,530 euthyroid participants.Central sensitivity to THs was assessed by the thyroid feedback quantile-based index (TFQI), parametric thyroid feedback quantile-based index (PTFQI), thyrotrophic thyroxine resistance index (TT4RI) and thyroid-stimulating hormone index (TSHI), while FT3/FT4 was evaluated to assess peripheral sensitivity. Multivariable regression analysis and restricted cubic spline were performed to explore the association between sensitivity to THs and periodontitis. Threshold effect and subgroup analysis were also conducted.Mediation analysis was performed to estimate direct and indirect effects through 25(OH)D.Multivariable regression analysis indicated that central sensitivity to THs indices(per SD increase) were positively associated with periodontitis risk [TFQI: